2021
DOI: 10.1002/jcp.30404
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy reporter mouse analysis reveals increased mitophagy activity in disuse‐induced muscle atrophy

Abstract: Muscle disuse induces atrophy through increased reactive oxygen species (ROS) released from damaged mitochondria. Mitophagy, the autophagic degradation of mitochondria, is associated with increased ROS production. However, the mitophagy activity status during disuse-induced muscle atrophy has been a subject of debate. Here, we developed a new mitophagy reporter mouse line to examine how disuse affected mitophagy activity in skeletal muscles. Mice expressing tandem mCherry-EGFP proteins on mitochondria were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Application of mito -QC variants on mice has successfully revealed the complex nature of mitophagy in tissues in a range of defined contexts. ( Hoshino et al., 2019 ; McWilliams et al., 2016 , 2018a , 2018b , 2019 ; Singh et al., 2020 ; Vannini et al., 2019 ; Yamashita et al., 2021 ). However, whether mitophagy is affected by mitochondrial disease and aging has remained undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Application of mito -QC variants on mice has successfully revealed the complex nature of mitophagy in tissues in a range of defined contexts. ( Hoshino et al., 2019 ; McWilliams et al., 2016 , 2018a , 2018b , 2019 ; Singh et al., 2020 ; Vannini et al., 2019 ; Yamashita et al., 2021 ). However, whether mitophagy is affected by mitochondrial disease and aging has remained undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial deterioration is frequently observed in various types of muscle wasting [1,3,4,17,35] and mitochondrial diseases causing serious muscle atrophy [33]. Previous reports have clearly shown that, in denervated muscle, mitochondrial content and function are severely damaged [1,5].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are one of the causes of muscle atrophy associated with inactivity, and it has been shown that the number and activity of mitochondria in skeletal muscle are reduced by inactivity [1,2]. It has been suggested that the increase in reactive oxygen species (ROS) produced by mitochondrial abnormalities leads to increased muscle protein degradation [3] and increased matrix metallo proteinase due to changes in intracellular calcium ion con centrations lead to extracellular matrix degradation [4], resulting in progressive muscle atrophy. It has been reported that when denervation induces muscle atrophy in experimental animals, activities of PGC-1α, which is involved in mitochondrial biosynthesis, COXIV protein, which re ects mitochondrial mass [1,2], and citrate synthase (CS) are decreased; in addition, there is a quantitative decrease in mitochondrial enzyme activity [5].…”
Section: Introductionmentioning
confidence: 99%
“…The best characterized reporter mice are mt-Keima (with Keima directed to the mitochondrial matrix) and mito-QC (with tandem GFP-mCherry targeted to the OMM by the FIS1 anchor) (McWilliams et al, 2016;Sun et al, 2015). In a recent variation of the mito-QC reporter, GFP-mCherry is targeted to the OMM by the anchor of OMP25 rather than FIS1 (Yamashita et al, 2021). With this GFP-mCherry-OMP25 reporter, mitophagic flux can be followed as the ratio of monomeric mCherry to tandem GFP-mCherry-OMP25 on an immunoblot, as well as by fluorescence microscopy (Yamashita et al, 2021).…”
Section: Box 2 Measuring Mitophagy In Vivomentioning
confidence: 99%
“…In a recent variation of the mito-QC reporter, GFP-mCherry is targeted to the OMM by the anchor of OMP25 rather than FIS1 (Yamashita et al, 2021). With this GFP-mCherry-OMP25 reporter, mitophagic flux can be followed as the ratio of monomeric mCherry to tandem GFP-mCherry-OMP25 on an immunoblot, as well as by fluorescence microscopy (Yamashita et al, 2021). mt-Keima is sensitive for mitophagy but requires in vivo or ex vivo imaging in non-fixed tissues (Katayama et al, 2011;Sun et al, 2015), whereas mito-QC and mito-SRAI can be fixed (Katayama et al, 2020;McWilliams et al, 2016).…”
Section: Box 2 Measuring Mitophagy In Vivomentioning
confidence: 99%